2021
DOI: 10.1111/apha.13735
|View full text |Cite
|
Sign up to set email alerts
|

The genetic deletion of the Dual Specificity Phosphatase 3 (DUSP3) attenuates kidney damage and inflammation following ischaemia/reperfusion injury in mouse

Abstract: Aim: Dual Specificity Phosphatase 3 (DUSP3) regulates the innate immune response, with a putative role in angiogenesis. Modulating inflammation and perfusion contributes to renal conditioning against ischaemia/reperfusion (I/R). We postulate that the functional loss of DUSP3 is associated with kidney resistance to I/R. Methods: Ten C57BL/6 male WT and Dusp3 −/− mice underwent right nephrectomy and left renal I/R (30 min/48 hours). Renal injury was assessed based on serum levels of urea (BUN) and Jablonski scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…This approach has the potential to unravel unknown signaling mechanisms. It was found that following I/R, serum levels of urea were significantly lower in Dusp3 −/− versus wild‐type mice 3 . The authors conclude that Genetic inactivation of Dusp3 is associated with kidney conditioning against ischemia reperfusion that is possibly due to attenuated inflammation and improved perfusion 3 …”
mentioning
confidence: 95%
See 4 more Smart Citations
“…This approach has the potential to unravel unknown signaling mechanisms. It was found that following I/R, serum levels of urea were significantly lower in Dusp3 −/− versus wild‐type mice 3 . The authors conclude that Genetic inactivation of Dusp3 is associated with kidney conditioning against ischemia reperfusion that is possibly due to attenuated inflammation and improved perfusion 3 …”
mentioning
confidence: 95%
“…It was found that following I/R, serum levels of urea were significantly lower in Dusp3 −/− versus wild-type mice. 3 The authors conclude that Genetic inactivation of Dusp3 is associated with kidney conditioning against ischemia reperfusion that is possibly due to attenuated inflammation and improved perfusion. 3 When one does experimental research with fundamental questions, it is sometimes not easy for the researchers to see the bridge to therapeutic or diagnostic applications.…”
mentioning
confidence: 98%
See 3 more Smart Citations